PERBANYAKAN IN VITRO PISANG BARANGAN (Musa paradisiacal Var. Sapientum L.) PADA MEDIA MURASHIGE DAN SKOOG DENGAN PENAMBAHAN BENZYLAMINOPURIN - Tilaar, W.; Sompotan, saartje (EUGENIA, 2007)
ABSTRACT Tilaar, W. and S. Sompotan. 2007. Multiplication in vitro of Banana Crop (Musa paradisiacal var. Sapientum L.) in Murashige and Skoog Medium With Suplemented Benzyleaminopurine. Eugenia 13 (2):127-131. Â  The objectives of this research was to examine in vitro multiplication of Banana in Murashige and Skoog medium by supplementing Benzyleamynopurine. This research was conducted in May-August 2006 at Laboratorium Biotechnology Faculty of Agriculture Sam Ratulangi. A Randomized complete design was use with four replication on each treatment. The treatments were 0; 7,5; 10 and 12,5 ppm. The variables of observed were total shoot, shoot height, and total leaves. The data was analysis using analysis of variance. The result showed that there significant differences on variable total shoot and leaves total. However, there was not significant difference on shoot height. Â  Keywords: Multiplication in vitro, Murashige and Skoog Medium, Benzylaminopurin, Musa paradisiaca